A public health approach to reducing violence within the CARICOM region - Maharaj, Sandeep; Seepersad, Randy; Sooknanan, Joanna; Anderson, Simon; Franco, Darleen; Ramdass, Amrica; Seemungal, Terence (Frontiers in Public Health, 2024)
Widespread crime has become a worldwide problem so much so that violence is now ranked fourth globally in its contribution to disability-adjusted life years in the 10 to 24 age group. Homicides, a surrogate marker of violent crime, have shown an upward trend in almost all of the CARICOM countries, and homicide rates over the past 3 years have consistently increased, though the pattern of violence varies by country. This background has informed the need for greater emphasis on the need for a different approach to dealing with crime in the CARICOM region. The CARICOM governments recently hosted a symposium on crime and violence as a public health issue. The public health approach to crime has been used with measurable success in different parts of the world and, more recently in Trinidad, one of the CARICOM countries. The paper outlines the outcomes of the symposium and discusses its implications for the region.